Sterculiaceae – A critical appraisal on plant tissue culture studies in medicinally important plants - Deshpande, Harshal A; Bhalsing, Sanjivani R (Research in Biotechnology, 2015)
The members of Sterculiaceae are valuable source of different kinds of useful products like wood, medicine, fiber, firewood and timber suitable for furniture, as well as decorative plants, pharmaceutical products and aestic items. In recent years the relevance of plant tissue culture methods has gained thrust to meet the growing demands for pharmaceutical industries since the genetic diversity of medicinal plants is decreasing hap hazardously. Conventional propagation and high demand of planting material are the major constraints for the large scale multiplication of medicinal species which can be met economically and efficiently in short span of time by in vitro propagation. Micropropagation is an alternative means of propagation that can be engaged in the conservation of flora in relatively shorter time. Tissue culture is useful for multiplying and conserving the useful species which are difficult to regenerate and thus can be saved from extinction. There is an only partial advancement explored at the research level to suggest tissue culture studies in Sterculiaceae. Conclusively, this appraisal is the first of its kind which emphasizes the procedures available for in vitro propagation along with some of the remarkable achievements carried in some pharmaceutically and commercially important plants by in vitro culture techniques of plants from this family Keywords: Pharmaceutical, medicinal, propagation, in vitro, Sterculiaceae